Analisis Tingkat Kepuasan Pasien Rawat Jalan di Puskesmas Simpang IV Sipin Kota Jambi - Guspianto Guspianto; Maya Erni Lobat; Rizaliah Wardiah (Jurnal Kesmas Jambi, 2023)
Quality is a dynamic condition associated with products, services, people, processes and the environment that meet and exceed expectations. Patient satisfaction was closely related to the quality of health services. This study aims to analyze the level of satisfaction and priorities for improving the quality of services among outpatients at Puskesmas Simpang IV Sipin. The quantitative descriptive study with a cross-sectional approach was conducted through interviews with 106 patients who were met during a visit to the Puskesmas. Data analysis was conducted with univariate and Cartesius diagram analysis. The results of study obtained an outpatient satisfaction level at Puskesmas Simpang IV Sipin Health Center of 78.63% and it was recommended for Puskesmas Simpang IV Sipin to prioritize efforts to improve service quality by providing service instructions or information, improving administrative services, increasing service timeliness, and increasing accuracy. and accuracy in providing services.